Ecological–Coenotic features and Current Distribution Echinocystis lobata (Michx.) Torr. et A. Gray (Cucurbitaceae) in Ukraine - Koniakin Serhii; Budzhak Vasyl; Leshcheniuk Olena; Gubar Liubov (Ekológia (Bratislava), 2024)
The information on the spontaneous spread (1152 localities) of the invasive species Echinocystis lobata is summarized. It was found that this alien species is timed to coastal water biotopes, floodplain meadows, mesophytic forests, wetlands, as well as disturbed ecotopes. The syntaxonomic scheme of vegetation with the participation of E. lobata includes 13 classes, 7 orders, 8 alliances, and 8 associations. It is predicted that under the conditions of a temperature increase of 3 °C, there will likely be changes in the carbonate content (Ca), water regime (Hd) of the soil, thermal regime (Tm), and climate humidity (Om), which will cause a reduction in the secondary range of the species in Ukraine, and the changed acid regime of the soil will cause (Rc) its disappearance in some localities. The obtained data can be used to carry out preventive measures regarding the emergence and further distribution of E. lobata in new habitats with different degrees of anthropogenic transformation.